STRATEGI PEMASARAN HOME INDUSTRY DALAM MENINGKATKAN EKONOMI KELUARGA BERDASARKAN PERSPEKTIF EKONOMI ISLAM - Atim Matul Mahmudah; Kasmiati; Linawati Linawati (Institut Daarul Qur'an Jakarta, Indonesia, 2023)
The research was aimed at analyzing home industry strategies for improving the family economy from the perspective of Islamic economics, with a research focus on the home industry of